[Sea Birds Along Water at Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of sea birds along the sea surrounding Heimaey. The white birds cover the brown, layered platform above the black water in the foreground. A brown mountain covered in green grass in the background.